Mast Cell-Activated Bone Marrow Mesenchymal Stromal Cells Regulate Proliferation and Lineage Commitment of CD34+ Progenitor Cells - Allakhverdi, Zoulfia; Comeau, Michael R.; Armant, Myriam; Agrawal, Rachana; Woodfolk, Judith A.; Sehmi, Roma; Howie, Karen J.; Gauvreau, Gail M.; Delespesse, Guy (Frontiers in Immunology, 2013)
Background: Shortly after allergen exposure, the number of bone marrow and circulating CD34+ progenitors increases. We aim to analyze the possible mechanism whereby the allergic reaction stimulates bone marrow to release these effector cells in increased numbers. We hypothesize that mast cells may play a predominant role in this process. Objective: To examine the effect of IgE-activated mast cells on bone marrow mesenchymal stromal cells which regulate proliferation and differentiation of CD34+ progenitors. Methods: Primary mast cells were derived from CD34+ precursors and activated with IgE/anti-IgE. Bone marrow mesenchymal stromal cells were co-cultured with CD34+ progenitor cells and stimulated with IL1/TNF or IgE/anti-IgE activated mast cells in Transwell system. Results: Bone marrow mesenchymal stromal cells produce low level of TSLP under steady state conditions, which is markedly increased by stimulation with proinflammatory cytokines IL-1 and TNF or IgE-activated mast cells. The latter also triggers BM-MSCs production of G-CSF, and GM-CSF while inhibiting SDF-1. Mast cell-activated mesenchymal stromal cells stimulate CD34+ cells to proliferate and to regulate their expression of early allergy-associated genes. Conclusion and Clinical Relevance: This in vitro study indicates that IgE-activated mast cells trigger bone marrow mesenchymal stromal cells to release TSLP and hematopoietic growth factors and to regulate the proliferation and lineage commitment of CD34+ precursor cells. The data predict that the effective inhibition of mast cells should impair mobilization and accumulation of allergic effector cells and thereby reduce the severity of allergic diseases.